A correlational study to assess predictability of diabetes on the basis of different anthropometric and biochemical indicators - Sharma, Vivek; Gour, Neeraj; Sarkar, Poornima Dey; Tafseer, Sana (International Journal of Research in Medical Sciences, 2018)
Background: Obesity is a complex disorder that involves some degree of over-consumption1 coupled with a metabolic derangement. There are some direct and indirect anthropometric and bio chemical indicators which if measured can provide some clue about development of diabetes among vulnerable group of population. Methods: This observational cross sectional study was conducted in the Department of Biochemistry at MGM Medical College and MY Hospital. All the patients and controls were clinically examined, and routine biochemical tests were analyzed for all subjects. Results: Positive and significant correlation was found between BMI and FBS, HBA1C, Leptin, HOMA IR respectively, whereas negative correlation was found between BMI and adiponectin. Same way positive correlation was found between W/H ratio and Leptin, HOMA IR respectively and negative correlation was found with adiponectin. Conclusions: This is very much evident through this study that various anthropometric and biochemical indicators may be treated as prognostic predictor of diabetes either linked to obesity or not.